Wanted: Moral Courage in Canadian Child Welfare - Cindy Blackstock (First Peoples Child & Family Review, 2020)
Child welfare stifles change and innovation in a system that desperately needs it by promoting conformity and awarding subordination to bad ideas (Blackstock, 2009). If neglect means not doing the right thing for children even when you know better and can do better, and have the resources to do it, then too often child protection neglects First Nations children and their families. This essay explores whether emancipating moral courage in child protection is the key to ensuring good research translates into real benefits for First Nations families. This paper begins with a description of moral courage in child protection across the decades before drawing on my own experiences with moral courage in the child welfare field. It concludes with stories of how moral cowardice diminishes children and how moral courage uplifts them. Implications for research, policy and practice are discussed. Key words: First Nations children, youth, families; child welfare; child protection; moral courage; implications for research, policy and practice.